Spectroscopic and antibacterial studies of new octaazamacrocyclic complexes derived from carbohydrazide and isatin - Kumar, Krishan; Kamboj, Monika; Jain, Kiran; Singh, D. P. (Spectrochimica Acta Part A-Molecular and Biomolecular Spectroscopy, 2014)
A novel series of the macrocyclic complexes of the type: [M(C18H14N10O2)X-2], where M = Co(II), Ni(II), Cu(II) and Zn(II); X = Cl-, NO3- and CH3COO-, has been synthesized by template condensation of carbohydrazide and isatin in methanolic medium. The complexes were characterized by various physico-chemical techniques, such as elemental analyses, molar conductance measurements, magnetic measurements, and electronic, NMR, IR and EPR spectral studies. The low value of molar conductance indicates them to be non-electrolytes. Based on various studies, a distorted octahedral geometry was proposed for all the metal complexes. Metal complexes were tested for their in vitro antibacterial activities against some pathogenic bacterial strains and compared with standard antibiotic, Ciprofloxacin. Some of the tested complexes was found effective against Gram-positive bacterial strains. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Carbohydrazide; Isatin; Macrocyclic complexes; MIC; Template condensation

Recursive partitioning analysis and anti-tubercular screening of 3-aminopyrazine-2-carbohydrazide derivatives - Miniyar, Pankaj; Mahajan, Anand; Anuse, Dattatray; Kumar, Ashish; Barmade, Mahesh; Sarkar, Dhiman; Arkile, Manisha; Khedkar, Vijay (Letters in Drug Design & Discovery, 2019)
Background: Treating tuberculosis is a challenge due to the development of drug resistance. Hence, it is imperative to develop novel leads having high potency and efficacy to curb drug resistance. Methods: The present research work is focused on microwave-assisted synthesis of novel twenty-six 3-amino-N'-benzylidenepyrazine-2-carbohydrazide derivatives (3a-z), where, lyophilization technique was used for isolation of the major intermediate, 3-aminopyrazin-2-carbohydrazide. All synthesized compounds were subjected for anti-tubercular screening against Mycobacterium tuberculosis H37Ra by using XTT Reduction Menadione Assay (XRMA) protocol. Results: Out of 26 synthesized compounds, four N'-substitutedbenzaldehyde-3-amino-pyrazine-2-carbohydrazide derivatives viz. 3i, 3j 3v and 3z showed significant activity against M. tuberculosis H37Ra. The compounds 3i, 3j, 3v and 3z showed 99, 98, 92 and 87 % inhibition respectively as compared to 94% inhibition shown by the standard drug rifampicin. The MIC and IC50 values were in the range of 24.3-110 and 5.9-20.8 mu g/ml respectively. Conclusion: A classification model called Recursive Partitioning (RP) based on binary Quantitative Structure-Activity Relationship (QSAR) was derived for the establishment of structure-activity relationship (SAR). The predictions derived on the basis of RP model were found to be in agreement with anti-tubercular screening data.
Keywords: 3-aminopyrazine; anti-tubercular activity; Carbohydrazide; lyophilization; QSAR; recursive partitioning